Ceramic-metal composite molded part and preparation method thereof and wear-resistant part

In the preparation process of metal-based composite materials, the waste heat and pressurized composite molding technology of the ceramic preform are used to improve the interface bonding strength between metal and ceramics, and the problem of easy failure of existing materials is solved, and the cost-saving effect is achieved.

CN112620610BActive Publication Date: 2025-04-29SONGSHAN LAKE MATERIALS LAB +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202011645208.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-12-31
Publication Date
2025-04-29
Estimated Expiration
2040-12-31

AI Technical Summary

Technical Problem

The interface bonding strength of existing metal-based composite materials is not high, resulting in easy material failure.

Method used

By placing the sintered ceramic preform in the casting mold for metal melt pouring, the waste heat of the ceramic preform increases the metal melt wetting, and further enhances the interface bonding during the pressurized composite molding process.

Benefits of technology

The interface bonding strength between metal and ceramic is improved, the probability of material failure is reduced, and the use of high-cost ceramic particles is saved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112620610B_ABST
    Figure CN112620610B_ABST
Patent Text Reader

Abstract

A ceramic-metal composite molded part and a preparation method thereof and a wear-resistant part belong to the technical field of composite materials. The preparation method of the ceramic-metal composite molded part comprises: mixing ceramic particles and an adhesive and sintering them into a ceramic preform. While the ceramic preform retains residual heat after sintering, the ceramic preform is placed in a casting mold for pouring a metal melt, and after pouring, pressurized composite molding is performed. It can increase the interface bonding strength between metal and ceramic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of composite materials, and in particular to a ceramic-metal composite molded part and a preparation method thereof, as well as a wear-resistant part. Background Art

[0002] The failure modes of metal matrix composites include: matrix damage (cutting and furrowing deformation, fatigue spalling), ceramic particle damage (brittle fracture), and interface damage between particles and matrix (stripping). The three failure modes conform to the "barrel effect", and the weakest place is most likely to fail. In order to improve the failure problem of metal matrix composites, the prior art uses chemical activation to treat ZTA ceramic particles, and titanium-nickel is plated on the surface of ceramic particles to generate titanium-nickel alloy as a flexible transition layer between the metal matrix and the ceramic reinforcement to achieve the purpose of bonding. However, the bonding strength of the interface of the metal matrix composite obtained by this method is not high. Summary of the invention

[0003] The present application provides a ceramic-metal composite molded part and a preparation method thereof, as well as a wear-resistant part, which can increase the interface bonding strength between metal and ceramic.

[0004] The embodiment of the present application is implemented as follows:

[0005] In a first aspect, an embodiment of the present application provides a method for preparing a ceramic-metal composite molded part, comprising:

[0006] Mixing ceramic particles and a binder and sintering them into a ceramic preform;

[0007] When the ceramic preform retains residual heat after sintering, the ceramic preform is placed in a casting mold for pouring molten metal;

[0008] After pouring, pressurized composite molding is performed.

[0009] In a second aspect, an embodiment of the present application provides a ceramic-metal composite molded part, which is produced by the preparation method of the ceramic-metal composite molded part of the embodiment of the first aspect of the present application.

[0010] In a third aspect, an embodiment of the present application provides a wear-resistant part, a partial area of ​​the wear-resistant part is a ceramic-metal composite molded part of an embodiment of the second aspect of the present application.

[0011] The beneficial effects of the ceramic-metal composite molded part and the preparation method thereof and the wear-resistant part of the embodiment of the present application include:

[0012] The sintered ceramic preform has a high compressive strength after sintering, and is not easily damaged during the process of pressurized composite molding after pouring the molten metal, which is conducive to the filling of the molten metal. When the ceramic preform is placed in a casting mold for pouring the molten metal while maintaining the residual heat after sintering, the residual temperature of the ceramic preform can increase the infiltration of the molten metal and increase the interface bonding strength between the metal and the ceramic preform, so that the obtained ceramic-metal composite molded part is not prone to failure.

[0013] Part of the wear-resistant parts are ceramic-metal composite molded parts, which can reduce the use of high-cost ceramic particles and save costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0015] Figure 1 A schematic structural diagram of a first ceramic preform provided for a specific embodiment of the present application;

[0016] Figure 2 A schematic structural diagram of a second ceramic preform provided in a specific embodiment of the present application;

[0017] Figure 3 A schematic structural diagram of a third ceramic preform provided for a specific embodiment of the present application;

[0018] Figure 4 A schematic structural diagram of a fourth ceramic preform provided in a specific embodiment of the present application;

[0019] Figure 5 A schematic structural diagram of a fifth ceramic preform provided in a specific embodiment of the present application;

[0020] Figure 6 A schematic structural diagram of a sixth ceramic preform provided in a specific embodiment of the present application;

[0021] Figure 7 A schematic structural diagram of a seventh ceramic preform provided in a specific embodiment of the present application;

[0022] Figure 8 A schematic structural diagram of an eighth ceramic preform provided for a specific embodiment of the present application;

[0023] Fig. 9 A schematic structural diagram of a ninth ceramic preform provided in a specific embodiment of the present application;

[0024] Fig.10 A schematic diagram of the structure of a wear-resistant part provided for a specific implementation method of the present application;

[0025] Fig.11 This is an industrial CT test image of the ceramic-metal composite molded part of Example 1 of the present application;

[0026] Fig.12 This is an industrial CT test image of the ceramic-metal composite molded part of Example 1 of the present application;

[0027] Fig.13 This is an EDS energy spectrum scanning diagram of the ceramic-metal composite molded part of Example 1 of the present application;

[0028] Fig.14 This is a SEM image of the ceramic-metal composite molded part of Example 1 of the present application;

[0029] Fig.15 This is a fracture morphology diagram of the ceramic-metal composite molded part of Example 1 of the present application;

[0030] Fig.16 This is the wear diagram of the wear-resistant lining of the sand making machine of Example 5 of the present application after 98 hours of service;

[0031] Fig.17 This is the wear diagram of the wear-resistant lining of the sand making machine of comparative example 1 of the present application after 98 hours of service;

[0032] Fig.18 This is the wear diagram of the wear-resistant lining of the sand making machine of Example 5 of the present application after serving for 391 hours;

[0033] Fig.19 This is the wear diagram of the sand making machine wear-resistant lining of comparative example 1 of the present application after 391 hours of service.

[0034] Icons: 10-wear-resistant part; 11-ceramic preform; 111-filling hole. DETAILED DESCRIPTION

[0035] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0036] It should be noted that the A and / or B schemes in the embodiments of the present application refer to a single A scheme, a single B scheme, or a combination of A scheme and B scheme.

[0037] In order to improve the failure problem of metal-based composite materials, the inventors of the present application tried to generate new ceramic particle reinforcements or intermetallic compounds in situ in the metal matrix by inducing reactions between ceramic compounds through the heat of pouring metal solution. This method can increase the interfacial bonding strength, but the types of ceramics are limited, and it is necessary for the ceramic compounds to react, or for the ceramic particles to react with the metal solution.

[0038] However, the bonding strength of the interface of the metal matrix composite material obtained by treating ZTA ceramic particles by chemical activation, plating titanium and nickel on the surface of the ceramic particles, and generating a titanium-nickel alloy as a flexible transition layer between the metal matrix and the ceramic reinforcement to achieve bonding is not high.

[0039] Based on this, the embodiments of the present application provide a ceramic-metal composite molded part and a preparation method thereof, as well as a wear-resistant part.

[0040] The following is a detailed description of the ceramic-metal composite molded part and its preparation method and the wear-resistant part of the embodiment of the present application:

[0041] In a first aspect, an embodiment of the present application provides a method for preparing a ceramic-metal composite molded part, comprising:

[0042] Mixing ceramic particles and a binder and sintering them into a ceramic preform 11;

[0043] When the ceramic preform 11 retains residual heat after sintering, the ceramic preform 11 is placed in a casting mold for pouring molten metal; after pouring, pressurized composite molding is performed.

[0044] The sintered ceramic preform 11 has high compressive strength after sintering, and is not easily damaged during the process of pressurized composite molding after pouring the metal melt, which is conducive to the filling of the metal melt. The metal melt can be high chromium cast iron, ductile iron, high manganese steel and low alloy wear-resistant steel.

[0045] When the ceramic preform 11 retains residual heat after sintering, the ceramic preform 11 is placed in a casting mold for pouring molten metal. The residual temperature of the ceramic preform 11 can increase the infiltration of the molten metal and increase the interfacial bonding strength between the metal and the ceramic preform 11. After pressurized composite molding, the molten metal can effectively supplement the shrinkage of the ceramic preform 11 during the solidification process, reduce defects such as looseness and shrinkage cavities, and the ceramic preform 11 is more tightly bonded to the metal, which is not conducive to crack propagation. The resulting ceramic-metal composite molded parts are not prone to failure. In addition, the method of pressurized composite molding of the ceramic preform 11 and the molten metal has little restriction on the type of ceramic particles. Optionally, the pressure during pressurized composite molding is 100 to 300 MPa, and the holding time is 100 to 200 s. For example, the pressure is 100 MPa, 150 MPa, 200 MPa, 250 MPa or 300 MPa; and the holding time is 100 s, 120 s, 150 s, 180 s or 200 s.

[0046] In addition, the ceramic particles can be at least one of zirconia toughened alumina (ZTA), Al2O3, ZrO2, B4C, TiC, vanadium carbide (VC), ZrC, NbC, WC, SiC, Si3N4, AlN and TiB2. Exemplarily, the ceramic particles are zirconia toughened alumina particles.

[0047] Optionally, the particle size of the ceramic particles is 4 to 18 meshes. The packing density of the ceramic particles of this size is appropriate, so as to avoid the packing density being too high, which makes it difficult for the metal melt to enter the interior of the ceramic preform 11 and combine with the ceramic preform 11, and to avoid the packing density being too low, which makes the strength of the ceramic preform 11 too low. Exemplarily, the particle size of the ceramic particles is any one of 4 meshes, 5 meshes, 7 meshes, 10 meshes, 12 meshes, 14 meshes and 18 meshes, or the range between any two of them. Optionally, the particle size of the ceramic particles is 8 to 14 meshes.

[0048] In addition, the ceramic particles are optionally at least one of spherical, cubic and obtuse. Exemplarily, the ceramic particles are spherical and / or cubic. The edges and corners of the spherical and / or cubic ceramic particles are not particularly sharp. Compared with the obtuse ceramic particles, the spherical and cubic ceramic particles are not easy to wear under the actual service conditions of impact wear. Because if the ceramic particles have sharp edges and corners, under the actual service conditions of impact wear, the edges and corners are easily knocked off or broken, causing the ceramic particles to fall off.

[0049] Furthermore, the adhesive may be optionally high temperature inorganic glue and water glass, wherein the main component of the high temperature inorganic glue is alumina, and the high temperature inorganic glue and water glass make the ceramic particles bond together at high temperature and will not decompose at high temperature.

[0050] In addition, the inventors of the present application also tried to preheat the ceramic preform 11 that has been sintered to room temperature before pouring the molten metal. This method not only wastes energy and cost, but also the ceramic preform 11 after sintering is cooled down and then preheated. After the second heating, the bonding between the ceramic preform 11 and the metal matrix will be weakened.

[0051] In a possible implementation, the sintering temperature of the ceramic preform 11 is 200-1200°C, and the holding time is 0.5-1h. Under the temperature condition of 200-1200°C, the ceramic preform 11 can be successfully sintered, and the shrinkage of the ceramic preform 11 caused by too high a temperature is avoided, thereby affecting the performance of the ceramic preform 11. Exemplarily, the sintering temperature is one of 200°C, 300°C, 500°C, 600°C, 800°C, 900°C, 1000°C, 1100°C and 1200°C, or the range between any two thereof.

[0052] Optionally, the sintering temperature of the ceramic preform 11 is 800-1000° C. After sintering, the temperature of the ceramic preform 11 is also relatively high, and the ceramic preform 11 can maintain a relatively high residual temperature, thereby preventing the metal melt from solidifying too quickly due to the residual temperature being too low, which is not conducive to the combination of the metal and the ceramic preform 11 .

[0053] It should be noted that after the ceramic preform 11 is sintered, it can be placed in a casting mold for pouring molten metal without any cooling treatment. The cooling treatment in the embodiment of the present application refers to cooling by certain means, such as water cooling, cooling by blowing cold air, natural cooling in the air, etc.

[0054] Without cooling treatment, it takes some time to take out the sintered ceramic preform 11 and place it in a casting mold. Optionally, within 5s to 30min after the sintering of the ceramic preform 11 is completed, the ceramic preform 11 is placed in a casting mold for pouring molten metal. Within the time range of 5s to 30min, the ceramic preform 11 still retains a relatively high temperature, which is more conducive to the combination of the ceramic preform 11 and the molten metal. Exemplarily, after the sintering of the ceramic preform 11 is completed, the ceramic preform 11 is placed in a casting mold for pouring molten metal within 5s, 10s, 20s, 30s, 1min, 5min, 10min, 20min or 30min.

[0055] It is understandable that when the sintering temperature is high, the ceramic preform 11 can also be cooled. As long as the residual temperature of the ceramic preform 11 after the cooling treatment is still relatively high, the metal melt can be infiltrated and the bonding strength between the ceramic preform 11 and the metal melt is also high.

[0056] Further, in a possible implementation, the volume ratio of the ceramic preform 11 to the ceramic-metal composite molded part is 0.3 to 0.7: 1. The ceramic-metal composite molded part with this composition ratio has better wear resistance. Optionally, the volume ratio of the ceramic preform 11 to the ceramic-metal composite molded part is 0.45 to 0.65: 1.

[0057] In order to further improve the failure problem of ceramic-metal composite molded parts, after pressurized composite molding, the molded ceramic-metal composite molded parts are also subjected to quenching treatment, and then tempered after being kept at a temperature of 200 to 360°C for 1.5 to 2.5 hours. After quenching treatment, tempering after being kept at a temperature of 200 to 360°C for 1.5 to 2.5 hours can further eliminate the residual stress of the ceramic-metal composite molded parts and reduce the probability of cracking of the ceramic-metal composite molded parts. Optionally, the insulation temperature is any one of 200°C, 220°C, 250°C, 280°C, 300°C, 320°C, 340°C and 360°C, or a range between any two of them.

[0058] In a second aspect, an embodiment of the present application provides a ceramic-metal composite molded part, which is produced by the method for producing a ceramic-metal composite molded part of an embodiment of the present application.

[0059] Further, the ceramic preform 11 includes a plurality of filling holes 111, and the cross-section of the filling holes 111 includes one of a triangle, a rectangle, a circle, a regular hexagon and a wave, or the cross-section of the filling holes 111 includes two of a triangle, a prism, a rectangle, a regular pentagon, a regular hexagon and a regular octagon (refer to Figure 1-Figure 9 ).

[0060] For example, Figure 1 As shown, the cross-section of the filling hole 111 includes a regular pentagon and a prism. Three sides of the filling hole 111 with a regular pentagonal cross-section correspond to one side of the filling hole 111 with a regular pentagonal cross-section, and the remaining two sides correspond to one side of the filling hole 111 with a prism cross-section.

[0061] Furthermore, the five sides of the filling hole 111 with a regular pentagonal cross section respectively correspond to a side of the filling hole 111 with a regular pentagonal cross section.

[0062] like Figure 2 As shown, the filling holes 111 include a plurality of groups of filling hole groups arranged horizontally, the cross-sections of the filling holes 111 in the filling hole groups are regular triangles and regular hexagons, the two diagonals of the filling holes 111 with regular hexagonal cross-sections respectively correspond to the corners of a filling hole 111 with regular hexagonal cross-sections, and the cross-sections of the remaining filling holes 111 are regular triangles, and each group of filling holes is distributed vertically.

[0063] like Figure 3As shown, the cross-section of the filling hole 111 is a regular octagon and a square, and the four sides of the filling hole 111 with a square cross-section respectively correspond to one side of the filling hole 111 with a regular octagon cross-section.

[0064] like Figure 4 As shown, the cross section of the filling hole 111 is an equilateral triangle, and adjacent filling holes 111 with cross sections being equilateral triangles are side to side and corner to corner.

[0065] like Figure 5 As shown, the cross section of the filling hole 111 is a square, and adjacent filling holes 111 with square cross sections are side to side and corner to corner.

[0066] like Figure 6 and Figure 7 As shown, the cross section of the filling hole 111 includes a circle, and the filling holes 111 with a circular cross section are distributed at intervals in the ceramic preform.

[0067] like Figure 8 As shown, the cross section of the filling holes 111 is a regular hexagon, and the filling holes 111 with a regular hexagonal cross section are arranged in a honeycomb shape in the ceramic preform 11 .

[0068] like Fig. 9 As shown, the cross section of the filling hole 111 is wavy, and the structure is a bionic shape of the shell of the animal "armadillo".

[0069] The structures of the ceramic preforms 11 described above can all improve the wear resistance of the ceramic-metal composite molded parts. It should be noted that the boundary in the ceramic preform 11 may be an incomplete filling hole 111 .

[0070] In a third aspect, an embodiment of the present application provides a wear-resistant part 10, and a partial area of ​​the wear-resistant part 10 is a ceramic-metal composite molded part of an embodiment of the present application.

[0071] Part of the wear-resistant part 10 is a ceramic-metal composite molded part, which can reduce the use of high-cost ceramic particles and save costs. It should be noted that the ceramic-metal composite molded part can be freely designed and added to the wear-resistant part according to the situation, and the shape of the wear-resistant part 10 can be diverse.

[0072] For example, the wear-resistant part 10 is plate-shaped, and the corners of the plate-shaped wear-resistant part 10 are ceramic-metal composite molded parts (such as Fig.10 shown).

[0073] The ceramic-metal composite molded part and its preparation method and the wear-resistant part of the present application are further described in detail below in conjunction with the embodiments.

[0074] Example 1

[0075] This embodiment provides a ceramic-metal composite molded part, and the preparation method thereof includes the following steps:

[0076] 100 parts by weight of ZTA ceramic particles with a particle size of 8 to 14 meshes are stirred and mixed with 4 parts by weight of high-temperature inorganic glue and 4 parts by weight of water glass to obtain a mixture, the mixture is placed in a metal mold, and then the metal mold and the mixture are placed in a muffle furnace for sintering to obtain a ceramic preform, the sintering temperature is 900°C, and the insulation time is 0.5h.

[0077] After sintering, the ceramic preform is placed in a casting mold within 20 seconds for high chromium cast iron melt casting. The temperature of the high chromium cast iron melt is 1650°C, and a zirconium oxide filter is used to purify the high chromium cast iron melt before casting.

[0078] After pouring, the hydraulic press head is used to extrude at a pressure of 150 MPa, and the pressure holding time is 150 seconds. After the high chromium cast iron melt is completely solidified, it is demolded, quenched after demolding, and then kept at 350°C for 2 hours before being air-cooled to obtain a ceramic-metal composite molded part.

[0079] The ceramic preform of this embodiment is as follows Figure 3 As shown, the volume of the ceramic preform accounts for 50% of the volume of the ceramic-metal composite molded part.

[0080] Example 2

[0081] This embodiment provides a ceramic-metal composite molded part, and the preparation method thereof includes the following steps:

[0082] 100 parts by weight of ZTA ceramic particles with a particle size of 4 to 10 meshes are stirred and mixed with 4 parts by weight of high-temperature inorganic glue and 4 parts by weight of water glass to obtain a mixture, the mixture is placed in a metal mold, and then the metal mold and the mixture are placed in a muffle furnace for sintering to obtain a ceramic preform, the sintering temperature is 1000°C, and the insulation time is 0.5h.

[0083] After sintering, the ceramic preform is placed in a casting mold within 20 seconds for high chromium cast iron melt casting. The temperature of the high chromium cast iron melt is 1600°C, and a zirconium oxide filter is used to purify the high chromium cast iron melt before casting.

[0084] After pouring, the hydraulic press was used to extrude the mold at a pressure of 200 MPa for 90 seconds. After the high-chromium cast iron melt was completely solidified, it was demolded, quenched, and then kept at 280°C for 2 hours before being air-cooled to obtain a ceramic-metal composite molded part.

[0085] The ceramic preform of this embodiment is as follows Figure 4As shown, the volume of the ceramic preform accounts for 50% of the volume of the ceramic-metal composite molded part.

[0086] Example 3

[0087] This embodiment provides a ceramic-metal composite molded part, and the preparation method thereof includes the following steps:

[0088] 100 parts by weight of ZrO2 ceramic particles with a particle size of 4 to 10 meshes are stirred and mixed with 4 parts by weight of high-temperature inorganic glue and 4 parts by weight of water glass to obtain a mixture, the mixture is put into a metal mold, and then the metal mold and the mixture are put into a muffle furnace for sintering to obtain a ceramic preform, the sintering temperature is 700°C, and the insulation time is 0.5h.

[0089] After sintering, the ceramic preform is placed in a casting mold within 20 seconds for high chromium cast iron melt casting. The temperature of the high chromium cast iron melt is 1700°C, and a zirconium oxide filter is used to purify the high chromium cast iron melt before casting.

[0090] After pouring, the hydraulic press head is used to extrude at a pressure of 100 MPa, and the pressure holding time is 120 seconds. After the high chromium cast iron melt is completely solidified, it is demolded, quenched after demolding, and then kept at 260°C for 2 hours before being air-cooled to obtain a ceramic-metal composite molded part.

[0091] The ceramic preform of this embodiment is as follows Figure 2 As shown, the volume of the ceramic preform accounts for 30% of the volume of the ceramic-metal composite molded part.

[0092] Example 4

[0093] This embodiment provides a ceramic-metal composite molded part, and the preparation method thereof includes the following steps:

[0094] 100 parts by weight of SiC ceramic particles with a particle size of 4 to 12 meshes are stirred and mixed with 4 parts by weight of high-temperature inorganic glue and 4 parts by weight of water glass to obtain a mixture, the mixture is placed in a metal mold, and then the metal mold and the mixture are placed in a muffle furnace for sintering to obtain a ceramic preform, the sintering temperature is 200°C, the insulation time is 1 hour, and after the sintering is completed, the temperature of the muffle furnace is adjusted to 700°C and the insulation time is 10 minutes.

[0095] The ceramic preform is placed in a casting mold within 20 seconds for high chromium cast iron melt casting. The temperature of the high chromium cast iron melt is 1680°C, and a zirconium oxide filter is used to purify the high chromium cast iron melt before casting.

[0096] After pouring, the hydraulic press head is used to extrude at a pressure of 150MPa, and the holding time is 120s. After the high chromium cast iron melt is completely solidified, it is demolded, quenched after demolding, and then kept at 360℃ for 2h before being air-cooled to obtain a ceramic-metal composite molded part.

[0097] The ceramic preform of this embodiment is as follows Figure 1 As shown, the volume of the ceramic preform accounts for 40% of the volume of the ceramic-metal composite molded part.

[0098] Example 5

[0099] Example 5 provides a wear-resistant part, which is a wear-resistant lining of a sand making machine. The wear-resistant lining of the sand making machine of Example 5 is made of the ceramic-metal composite molded part of Example 1 of the present application.

[0100] Comparative Example 1

[0101] This comparative example provides a sand making machine wear-resistant lining made of high chromium cast iron.

[0102] Test Example 1

[0103] The ceramic-metal composite molded part of Example 1 was tested by 450kV industrial CT. The test results are as follows: Fig.11 and Fig.12 As shown. Among them, Fig.11 and Fig.12 Available in different scales.

[0104] from Fig.11 and Fig.12 It can be seen that the ceramic-metal composite molded part of Example 1 of the present application has fewer shrinkage cavities and the size of the shrinkage cavities is smaller.

[0105] Test Example 2

[0106] The ceramic-metal composite molded part of Example 1 was subjected to EDS energy spectrum scanning, and the results are as follows: Fig.13 As shown, Fig.13 IMG1(1st) and IMG1 in FIG. 5 are the overall shape structures of the ceramic-metal composite molded parts, and the others represent the distribution of various elements.

[0107] from Fig.13 It can be seen from the results that the ceramic preform and the metal matrix in the ceramic-metal composite molded part of Example 1 of the present application are tightly combined, and there are no defects such as holes in the middle.

[0108] Test Example 3

[0109] The ceramic-metal composite molded part of Example 1 was observed under an electron scanning microscope to obtain a SEM image, and the results are as follows: Fig.14 shown.

[0110] from Fig.14 It can be seen from the results that in the ceramic-metal composite molded part of Example 1 of the present application, the ceramic preform and the metal matrix are tightly combined, and the ceramic preform and the metal matrix have a mechanical anchoring effect.

[0111] Test Example 4

[0112] The impact fracture toughness of the ceramic-metal composite molded part of Example 1 of 10 mm × 10 mm × 55 mm was tested according to ISO 946-1975 gray cast iron unnotched impact test standard. The impact fracture toughness reached 2 J / cm 2 The fracture morphology was observed using an electron scanning microscope, and the morphology is shown in Figure 15.

[0113] from Fig.15 It can be seen that most of the ceramic particles in the porcelain-metal composite molded part of Example 1 of the present application did not fall off, but were directly broken, which also shows that the bonding strength between the metal matrix and the ceramic particles in the porcelain-metal composite molded part of Example 1 of the present application is high.

[0114] Test Example 5

[0115] The wear-resistant lining plate of the sand making machine of Example 5 and the wear-resistant lining plate of the sand making machine of Comparative Example 1 were subjected to comparative tests at the site where the sand making machine was used (the material was hard granite). The results are as follows: Figure 16-Figure 19 As shown. Among them, Fig.16 This is the wear diagram of the sand making machine wear-resistant lining of Example 5 after 98 hours of service. Fig.17 This is the wear diagram of the sand making machine wear-resistant lining of comparative example 1 after 98 hours of service; Fig.18 This is the wear diagram of the sand making machine wear-resistant lining of Example 5 after serving for 391 hours. Fig.19 This is the wear diagram of the sand making machine wear-resistant lining of comparative example 1 after 391 hours of service.

[0116] from Figure 16-Figure 19 It can be seen that within the same period of time, the wear of the wear-resistant lining of the sand making machine in Example 5 of the present application is lighter than that of the wear-resistant lining of the sand making machine, which shows that the wear-resistant lining of the sand making machine in Example 5 of the present application has better wear resistance than the wear-resistant lining of the sand making machine in Comparative Example 1.

[0117] The above description is only a specific embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing a ceramic-metal composite molded part, characterized in that: include: Mixing ceramic particles and a binder and sintering them into a ceramic preform; the binder includes high-temperature inorganic glue and water glass; After the ceramic preform is sintered, the ceramic preform is placed in a casting mold for pouring a molten metal without cooling the ceramic preform; After pouring, pressurized composite molding is performed, the pressure is 100-300 MPa, and the pressure holding time is 100-200 seconds to obtain a ceramic-metal composite molded part; The sintering temperature of the ceramic preform is 600-1200°C; The volume ratio of the ceramic preform to the ceramic-metal composite molded part is 0.3-0.7:1; After the pressurized composite molding, the formed ceramic-metal composite molded part is quenched and then tempered after being kept at a temperature of 200-360° C. for 1.5-2.5 hours.

2. The method for preparing a ceramic-metal composite molded part according to claim 1, characterized in that: The sintering temperature of the ceramic preform is 800-1000° C., and the heat preservation time is 0.5-1 h.

3. The method for preparing a ceramic-metal composite molded part according to claim 1 or 2, characterized in that: After the sintering of the ceramic preform is completed, the ceramic preform is placed in a casting mold for pouring molten metal within 5s to 30s.

4. The method for preparing a ceramic-metal composite molded part according to claim 1 or 2, characterized in that: The particle size of the ceramic particles is 4-18 meshes.

5. The method for preparing a ceramic-metal composite molded part according to claim 4, characterized in that: The particle size of the ceramic particles is 8-14 meshes.

6. The method for preparing a ceramic-metal composite molded part according to claim 4, characterized in that: The shape of the ceramic particles is selected from one or more of spherical, cubic and obtuse shapes.

7. The method for preparing a ceramic-metal composite molded part according to claim 1, characterized in that: The volume ratio of the ceramic preform to the ceramic-metal composite molded part is 0.45-0.65:

1.

8. A ceramic-metal composite molded part, characterized in that: The ceramic-metal composite molded part is prepared by the preparation method of any one of claims 1 to 7.

9. The ceramic-metal composite molded part according to claim 8, characterized in that: The ceramic preform includes a plurality of filling holes, wherein the cross-section of the filling holes includes one of a triangle, a rectangle, a circle, a regular hexagon and a wave, or the cross-section of the filling holes includes two of a triangle, a prism, a rectangle, a regular pentagon, a regular hexagon and a regular octagon.

10. A wear-resistant part, characterized in that: A partial area of ​​the wear-resistant part is the ceramic-metal composite molded part according to claim 8 or 9.

Citation Information

Patent Citations

  • Method for preparing selectively enhanced aluminum-based composite from ceramic particles

    CN102225461A

  • Method for manufacturing low-cost and high-wear-resistance ceramal composite liner plate

    CN105149875A

  • Ceramic-metal composite molded part and wear-resistant part

    CN215315643U